2019
DOI: 10.3390/v11030271
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Small RNA Responses to West Nile and Insect-Specific Virus Infections in Aedes and Culex Mosquito Cells

Abstract: Small RNA mediated responses are essential for antiviral defence in mosquitoes, however, they appear to differ per virus-vector combination. To further investigate the diversity of small RNA responses against viruses in mosquitoes, we applied a small RNA deep sequencing approach on five mosquito cell lines: Culex tarsalis CT cells, Aedes albopictus U4.4 and C6/36 cells, Ae. aegypti Aag2 cells (cleared from cell fusing agent virus and Culex Y virus (CYV) by repetitive dsRNA transfections) and Ae. pseudoscutella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 77 publications
10
83
0
Order By: Relevance
“…2) come from four different studies and five different Culicinae mosquito species (Chandler et al 2015;Cook et al 2013;Shi et al 2016Shi et al , 2017; moreover, in several samples, viral RNA accounts for >0.1 per cent (in one case, >2%) of total non-ribosomal RNA reads, which may be unlikely if the virus is infecting a contaminant (Shi et al 2016(Shi et al , 2017. Very recently, another narnavirus in this clade (MK628543.1; Culex narnavirus 1; 97 per cent nt identity to KP642120.1) was found to persistently infect a Culex tarsalis cell culture and also give rise to typical 21nt viral siRNAs with equal coverage of both strands, indicative of active infection (Gö ertz et al 2019). An ONLV2-related EVE has been previously reported for arthropods (Shi et al 2016), and we also identified sequences that clustered with rORFcontaining narnaviruses in WGS assembly data sets from several species of ant, the seven spot ladybird and the glassy winged sharpshooter.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2) come from four different studies and five different Culicinae mosquito species (Chandler et al 2015;Cook et al 2013;Shi et al 2016Shi et al , 2017; moreover, in several samples, viral RNA accounts for >0.1 per cent (in one case, >2%) of total non-ribosomal RNA reads, which may be unlikely if the virus is infecting a contaminant (Shi et al 2016(Shi et al , 2017. Very recently, another narnavirus in this clade (MK628543.1; Culex narnavirus 1; 97 per cent nt identity to KP642120.1) was found to persistently infect a Culex tarsalis cell culture and also give rise to typical 21nt viral siRNAs with equal coverage of both strands, indicative of active infection (Gö ertz et al 2019). An ONLV2-related EVE has been previously reported for arthropods (Shi et al 2016), and we also identified sequences that clustered with rORFcontaining narnaviruses in WGS assembly data sets from several species of ant, the seven spot ladybird and the glassy winged sharpshooter.…”
Section: Discussionmentioning
confidence: 97%
“…Since our original identification of long rORFs in the ONLV1 and ONLV2 genomes, besides sequences from Uromyces appendiculatus and Puccinia striiformis transcriptomes (Cook et al 2013), a number of other studies have discovered narnaviral genomes containing similar rORFs (Chandler et al 2015;Shi et al 2016Shi et al , 2017Viljakainen et al 2018;Gö ertz et al 2019). These rORFcontaining sequences appear not to form a monophyletic group, although they do show considerable phylogenetic clustering.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, evidence was put forward that at least some narnaviruses are true arthropod viruses: for example, the group of alphanarnaviruses comprising (Figure 2) come from four different studies and five different Culicinae mosquito species (Chandler et al 2015;Cook et al 2013;Shi et al 2016;Shi et al 2017); moreover, in several samples, viral RNA accounts for >0.1% (in one case, >2%) of total non-ribosomal RNA reads, which appears unlikely if the virus is infecting a contaminant (Shi et al 2016;Shi et al 2017). Very recently, another narnavirus in this clade (MK628543.1; Culex narnavirus 1; 97% nt identity to KP642120.1) was found to persistently infect a Culex tarsalis cell culture and also give rise to typical 21-nt viral siRNAs with equal coverage of both strands, indicative of active infection (Göertz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These infections were first observed in cultured yeast 2,3 . Subsequent metagenomic sequencing revealed narnaviruses in other fungi 4 , oomycetes 5 , mosquitoes [6][7][8][9] , other arthropods 10 , algae 11 , trypanosomatids [12][13][14] and potentially apicomplexans 15 , although the precise host species is not always clear. The known examples of narnaviruses are approximately 3 kb in size and code for a single protein, an RNA-dependent RNA polymerase (RdRp), with the exception of two putative bipartite narnaviruses 12,14,15 .…”
Section: Introductionmentioning
confidence: 99%